Damage control in the intensive care unit: what should the intensive care physician know and do? (Colombia Medica, 2021)
When trauma patients are admitted into the intensive care unit after undergoing damage control surgery, they generally present some degree of bleeding, hypoperfusion, and injuries that require definitive repair. Trauma patients admitted into the intensive care unit after undergoing damage control surgery can present injuries that require a definite repair, which can cause bleeding and hypoperfusion. The intensive care team must evaluate the severity and systemic repercussions in the patient. This will allow them to establish the need for resuscitation, anticipate potential complications, and adjust the treatment to minimize trauma-associated morbidity and mortality. This article aims to describe the alterations present in patients with severe trauma who undergo damage control surgery and considerations in their therapeutic approach. The intensivist must detect the different physiological alterations presented in trauma patients undergoing damage control surgery, mainly caused by massive hemorrhage. Monitor and support strategies are defined by the evaluation of bleeding and shock severity and resuscitation phase in ICU admission. The correction of hypothermia, acidosis, and coagulopathy is fundamental in the management of severe trauma patients.